Interstitial lung disease induced by fluoxetine: Systematic review of literature and analysis of Vigiaccess, Eudravigilance and a national pharmacovigilance database - Deidda, Arianna; Pisanu, Claudia; Micheletto, Laura; Bocchetta, Alberto; Del Zompo, Maria; Stochino, Maria Erminia (Pharmacological research, 2017)
[Display omitted] We investigated a pulmonary adverse drug reaction possibly induced by fluoxetine, the Interstitial Lung Disease, by performing a systematic review of published case reports on this subject, a review of the World Health Organization VigiAccess database, of the European EudraVigilance database and of a national Pharmacovigilance database (Italian Pharmacovigilance Network). The research found a total of seven cases linking fluoxetine to Interstitial Lung Disease in the literature. 36 cases of interstitial lung disease related to fluoxetine were retrieved from the VigiAccess database (updated to July 2016), and 36 reports were found in EudraVigilance database (updated to June 2016). In the Italian Pharmacovigilance database (updated to August 2016), we found only one case of Interstitial Lung Disease, codified as “pulmonary disease”. Our investigation shows that fluoxetine might be considered as a possible cause of Interstitial Lung Disease. In particular, although here we do not discuss the assessment of benefits and harms of fluoxetine, since this antidepressant is widely used, our review suggests that fluoxetine-induced Interstitial Lung Disease should be considered in patients with dyspnea, associated or not with dry cough, who are treated with this drug. An early withdrawn of fluoxetine could be useful to obtain a complete remission of this adverse drug reaction and special attention should be particularly devoted to long-term therapy, and to female and elderly patients. Although the spontaneous reporting system is affected by important limitations, drug post- marketing surveillance represents an important tool to evaluate the real world effectiveness and safety of drugs.